RUMAH PENCU DI KUDUS: Kajian Berdasarkan Tipologi dan Pola Sebaran - Imam Nazarudin (Berkala Arkeologi, 2012)
This study discusses about the traditional houses one of the houses contained in the Holy Pencu home. Pencu home has architectural joglo shaped and has a distribution contained in the Holy Ghost and Wetan Kulon. This study aimed to objective is to know the types of Pencu houses resulting from the classification based on arsitectural, and able to explain the difference between Kudus Kulon and Kudus Wetan Pencu house based on distribution patterns. The results of this study produced six classifications based on the architecture of the house spread Pencu contained Kudus, namely types A, B, C, D, E, and F. The presence of the type of Pencu houses indicate levels of hierarchy in the distribution of Pencu house in Kudus. Kudus Kulon, has more types of variation and the density is very high compared with that of the Kudus Wetan. Pencu type of house it shows the pattern of settlement distribution center that has a pattern of getting away from the central location of the lower levels of the type of home Pencu. This condition indicates that the Holy of Kulon is the axis / central of the traditional culture of the Kudus people.